Integrasi Kearifan Budaya Bugis: Malebbi Warekkadanna Makkiade Ampena dalam Membangun Jiwa Agama Mahasiswa di IAIN Parepare - Mukhtar Mas'ud; Fikri Fikri; Neti S Neti S; Sitti Jamilah; Muzakkir Muzakkir (Al-Ulum, 2020)
This study focuses on integrating Bugis culture malebbi warekkadanna makkiade ampena in building the religious spirit of students. This qualitative research with sociological, anthropological, and religious approaches was applied using in-depth interviews, observation, and documentation at IAIN Parepare. The results showed that the religious studies at IAIN Parepare as an extra activity apart from lectures could manifest the personality of having intelligence, depth of knowledge, and religious spirit as a student with good moral character. The integration of Bugis culture malebbi warekkadanna makkiade ampena with the religious studies transforms students into educated human beings with good moral character, loves religion and culture in the context of being able to speak and act politely.